Single-Dose Radiation Therapy Without Additional Surgery as a Treatment for Heterotopic Ossification Developing After Transfemoral Amputation. (2nd November 2022) - Zorn, Devon; Lombardo, Joseph; Poiset, Spencer; Gutman, Michael; Cappelli, Louis; Hurwitz, Mark; Ankam, Nethra
Abstract: Heterotopic ossification is the development of mature lamellar bone in soft tissues. Heterotopic ossification can occur in up to 23% of patients after amputation. Heterotopic ossification is often painful, causing significant dysfunction. While radiotherapy is used to prevent heterotopic ossification before formation, there is a dearth of literature on using radiotherapy to treat existing heterotopic ossification. This case report describes the use of late radiotherapy for the management of existing heterotopic ossification that developed after a transfemoral amputation. A 61-yr-old woman with peripheral artery disease of her bilateral lower limbs status post stenting and ultimately left transfemoral amputation was diagnosed with symptomatic heterotopic ossification limiting her function. Another surgery was not felt to be warranted. She was not improving with medical therapy and was prescribed 800 cGy in one fraction. After treatment, she experienced significant relief in her pain, allowing her to resume physical therapy and use of her prosthesis. There are no other published examples of using radiation alone for treatment of heterotopic ossification formation after transfemoral amputation without surgical revision of the bone formation. Our case shows possible utility in single-dose radiation as a treatment to prevent progression of heterotopic ossification, especially when limiting functional progress.